Time averaged and fluctuating heat transfer measurements in an atomising mist jet nozzle - PERSOONS, TIM; MURRAY, DARINA; BYRNE, GERARD (ASME, 2009)
Much is already known about the heat transfer characteristics of impinging air jets, and they are widely used in many engineering applications. There currently exist many correlations describing such characteristics. However, the complex internal structure of many nozzles can lead these to produce results which deviate from those predicted by correlations. One such nozzle is currently used in this research group to produce a water mist flow and this paper describes the experimental characteristics of its single phase behaviour.
ASME International Mechanical Engineering Congress and Exposition
PUBLISHED
paper IMECE2009-11244
Florida, USA
Keywords: mist jet; heat transfer; Smart & Sustainable Planet; Telecommunications